Karakteristik Kimia dan Organoleptik Rengginang Formulasi Biji Hotong dengan Tepung Jagung (Zea mays L.) - Lakalay, Anna V; Ega, La; Augustyn, Gelora H (Universitas Pattimura, 2024)
Rengginang hotong seeds are a traditional Indonesian snack made from Setaria italica seeds. Corn flour was added to rengginang hotong seed formulations to diversify the uses of dry corn seeds. This study aimed to determine the optimal formulation of rengginang hotong seeds with corn flour in terms of chemical and organoleptic properties. A randomized complete block design with three replications was used to evaluate five formulations of rengginang hotong seeds with varying proportions of corn flour (20%, 40%, 60%, 80%, and 100%). The chemical properties measured were water content, protein content, fat content, ash content, and carbohydrate content. The organoleptic properties measured were color, taste, aroma, texture, and overall acceptability. The results showed that the formulation with 60% corn flour had the highest overall acceptability, with the following chemical composition: water content 10.373%, protein content 9.321%, fat content 6.150%, ash content 8.251%, and carbohydrate content 76.132%. The organoleptic properties of the formulation with 60% corn flour were as follows: color 3.64, taste 3.88, aroma 3.72, texture 3.36, and overall acceptability 3.2.